Ventral Hippocampal-Prefrontal Interaction Affects Social Behavior via Parvalbumin Positive Neurons in the Medial Prefrontal Cortex - Qingtao Sun; Xiangning Li; Anan Li; Jianping Zhang; Zhangheng Ding; Hui Gong; Qingming Luo (iScience, 2020)
Summary: Ventral hippocampus (vHIP) and medial prefrontal cortex (mPFC) are both critical regions for social behaviors. However, how their interactions affect social behavior is not well understood. By viral tracing, optogenetics, chemogenetics, and fiber photometry, we demonstrated that inhibition of vHIP or direct projections from vHIP to mPFC impaired social memory expression. Via rabies retrograde tracing, we found that all three major GABAergic neurons in mPFC received direct inputs from vHIP. Activation of parvalbumin positive (PV+) neurons in mPFC but not somatostatin positive (SST+) neurons can rescue the social memory impairment caused by vHIP inhibition. Furthermore, fiber photometry results demonstrated that social behaviors preferentially recruited PV+ neurons and inhibition of hippocampal neurons disrupted the activity of PV+ neurons during social interactions. These results revealed a new mechanism of how vHIP and mPFC regulate social behavior in complementarity with the existing neural circuitry mechanism. : Behavioral Neuroscience; Neuroscience; Systems Neuroscience Subject Areas: Behavioral Neuroscience, Neuroscience, Systems Neuroscience